Implementation of Decision Support System for Scholarship Recipients at Bank Indonesia - Megah Sari, Dian; Arifin, Nurhikma; Nurfitrianingsih; Yusuf, Andi M (Ceddi Journal of Education, 2022)
The Bank Indonesia Scholarship is a social program by Bank Indonesia that provides tuition assistance for undergraduate students at various State Universities (PTN). However, the process of determining scholarship recipients has often been inaccurate, primarily because the selection process has not utilized systematic tools or methods. To address this issue, a system has been designed to enhance the accuracy of scholarship recipient selection. The selection process requires precision and is time-consuming, as each student's data must be compared according to predetermined criteria, making it susceptible to human error. Currently, Bank Indonesia has not implemented a method to facilitate the selection of potential scholarship recipients, relying instead on manual comparisons. This study introduces the application of the Fuzzy Multiple Attribute Decision Making (FMADM) method combined with Simple Additive Weighting (SAW) to improve the selection process. The FMADM method is employed to identify the best alternatives from a set of options based on predefined criteria, while the SAW method is used to rank these alternatives. The findings of this study serve as a decision-making tool to recommend scholarship recipients, contributing to the development of knowledge in the field of decision support systems. By integrating these methods, the research advances the accuracy and efficiency of scholarship selection processes, offering a model that can be adapted for similar contexts in educational funding and beyond.